2010
DOI: 10.1007/s10603-010-9144-3
|View full text |Cite
|
Sign up to set email alerts
|

Deceiving Our Minds: A Qualitative Exploration of the Money Illusion in Post-redenomination Ghana

Abstract: Money illusion, Redenomination, Ghana, Currency,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…In addition, the psychological effects (perceptions) of society on this policy tend to be good. Then, previous research was done by Dzokoto et al (2010). This study analyzes the existence of money illusion that occurred in Ghana after the redenomination policy.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the psychological effects (perceptions) of society on this policy tend to be good. Then, previous research was done by Dzokoto et al (2010). This study analyzes the existence of money illusion that occurred in Ghana after the redenomination policy.…”
Section: Resultsmentioning
confidence: 99%
“…Kecenderungan ini dapat membuat perubahan persepsi dan tingkah laku pada masyarakat ketika kebijakan redenominasi dilakukan. Contohnya adalah terjadinya perubahan daya beli konsumen di Irlandia dan Ghana (Ranyard, Burgyone, Saldanha & Routh, 2005) dan kesalahan mempersepsikan harga suatu barang yang membuat terjadinya perubahan pola perilaku pembelian barang (Dzokoto, Mensah, Twum-Asante, Opare-Henaku, 2010).…”
Section: Pendahuluanunclassified
“…It was found that currency with lower nominal value makes prices appear smaller than prices expressed in currency with higher nominal value (Raghubir, Srivastava, 2002;van Raaij, van Rijen, 2003;Dzokoto et al, 2010). It means that individuals spend their budgets more easily while using currency with lower nominal value.…”
Section: The Impact Of Money Illusion On Individuals' Economic Behaviourmentioning
confidence: 99%